Clinical performance and head-to-head comparison of CSF p-tau235 with p-tau181, p-tau217 and p-tau231 in two memory clinic cohorts - Lantero-Rodriguez J; Vrillon A; Fernández-Lebrero A; Ortiz-Romero P; Snellman A; Montoliu-Gaya L; Brum WS; Cognat E; Dumurgier J; Puig-Pijoan A; Navalpotro-Gómez I; García-Escobar G; et al. (BMC, 2025)
Background: Cerebrospinal fluid (CSF) p-tau235 is a novel biomarker highly specific of Alzheimer's disease (AD). However, CSF p-tau235 has only been studied in well-characterized research cohorts, which do not fully reflect the patient landscape found in clinical settings. Therefore, in this multicentre study, we investigated the performance of CSF p-tau235 to detect symptomatic AD in clinical settings and compared it with CSF p-tau181, p-tau217 and p-tau231.
Methods: CSF p-tau235 was measured using an in-house single molecule array (Simoa) assay in two independent memory clinic cohorts: Paris cohort (Lariboisiere Fernand-Widal University Hospital Paris, France; n=212) and BIODEGMAR cohort (Hospital del Mar, Barcelona, Spain; n=175). Patients were classified by the syndromic diagnosis (cognitively unimpaired [CU], mild cognitive impairment [MCI] or dementia) and their biological diagnosis (amyloid-beta [Aβ]+ or Aβ -) Both cohorts included detailed cognitive assessments and CSF biomarker measurements (clinically validated core AD biomarkers [Lumipulse CSF Aβ1-42/40 ratio, p-tau181 and t-tau] and in-house developed Simoa CSF p-tau181, p-tau217 and p-tau231).
Results: High CSF p-tau235 levels were strongly associated with CSF amyloidosis regardless of the clinical diagnosis, being significantly increased in MCI Aβ+ and dementia Aβ+ when compared with all other Aβ - groups (Paris cohort: P <0.0001 for all; BIODEGMAR cohort: P <0.05 for all). CSF p-tau235 was pronouncedly increased in the A+T+ profile group compared with A-T- and A+T- groups (P <0.0001 for all). Moreover, CSF p-tau235 demonstrated high diagnostic accuracies identifying CSF amyloidosis in symptomatic cases (AUCs=0.86 to 0.96) and discriminating AT groups (AUCs=0.79 to 0.98). Overall, CSF p-tau235 showed similar performances to CSF p-tau181 and CSF p-tau231 when discriminating CSF amyloidosis in various scenarios, but lower than CSF p-tau217. Finally, CSF p-tau235 associated with global cognition and memory domain in both cohorts.
Conclusions: CSF p-tau235 was increased with the presence of CSF amyloidosis in two independent memory clinic cohorts. CSF p-tau235 accurately identified AD in both MCI and dementia patients. Overall, the diagnostic performance of CSF p-tau235 was comparable to that of other CSF p-tau measurements, indicating its suitability to support a biomarker-based AD diagnosis in clinical settings.